2021
DOI: 10.1371/journal.pone.0254359
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy into the battle of supporting or opposing reopening amid the COVID-19 pandemic on Twitter: A temporal and spatial analysis

Abstract: Reopening amid the COVID-19 pandemic has triggered a battle on social media. The supporters perceived that the lockdown policy could damage the economy and exacerbate social inequality. By contrast, the opponents believed it was necessary to contain the spread and ensure a safe environment for recovery. Anatomy into the battle is of importance to address public concerns, beliefs, and values, thereby enabling policymakers to determine the appropriate solutions to implement reopening policy. To this end, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
(68 reference statements)
1
7
1
Order By: Relevance
“…However, despite their promising potentials, these kinds of data are relatively underlooked in the existing scholarly literature. Saleh et al [ 56 ] as well as Oyebode and coworkers [ 57 ] and Li and colleagues [ 58 ], confirming our findings, reported that a significant portion of tweets and posts on social networkers expressed fear of the societal implications of the COVID-19 pandemic, conveying worries and concerns for the loss of income, unemployment, inflation, and financial burden/hardship.…”
Section: Discussionsupporting
confidence: 89%
“…However, despite their promising potentials, these kinds of data are relatively underlooked in the existing scholarly literature. Saleh et al [ 56 ] as well as Oyebode and coworkers [ 57 ] and Li and colleagues [ 58 ], confirming our findings, reported that a significant portion of tweets and posts on social networkers expressed fear of the societal implications of the COVID-19 pandemic, conveying worries and concerns for the loss of income, unemployment, inflation, and financial burden/hardship.…”
Section: Discussionsupporting
confidence: 89%
“…Different from previous research conclusions on the single development of emotional changes [ 16 ], we found that the positive emotions and negative emotions of social media users affected by China’s sudden opening-up policy are different in the inflection point of emotional evolution and the performance of events of concern.…”
Section: Discussioncontrasting
confidence: 99%
“…Such studies show that large numbers of citizens express support for reopening lockdown policies but express emotional concerns about their implementation [ 15 ]. This is a contradictory emotional expression that requires specific analysis of the factors that generate user emotions [ 16 ]. There are studies analyzing the characteristics and influencing factors of Twitter users’ emotions towards the reopening of the economy [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we sought to understand public emotional responses by county to public health policies implemented in the early weeks of the COVID-19 pandemic. Other studies have examined state-level public perceptions regarding support or opposition [16]. A better understanding of the public's emotional response to policies at the county level may offer important insights for policymakers as they consider how to tailor implementation and communication strategies in their areas and the spillover effects of their efforts in surrounding communities.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have utilized social media data to gauge the collective reactions of the public and study responses to various policy interventions [12][13][14]. Researchers have also studied Twitter 9.0 data to understand disinformation during the pandemic [15] and support for and opposition to reopening policies [16].…”
Section: Introductionmentioning
confidence: 99%